1953
DOI: 10.1084/jem.98.6.583
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Transplanted Lymphomas Induced in Vivo by Means of Normal Guinea Pig Serum

Abstract: In an extension of the experimental studies recorded in an associated paper; attempts were made to isolate and characterize the constituent of guinea pig serum responsible for inducing regression of transplanted lymphomas in vivo. The active material was precipitated readily from the whole serum, along with some of the globulins, by means of ammonium sulfate in concentrations of 2.0 molar or greater; it withstood heating at 56°C. for 20 or 30 minutes, but was inactivated upon heating at 66°C. for similar perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
10

Year Published

1963
1963
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(56 citation statements)
references
References 12 publications
0
46
0
10
Order By: Relevance
“…(2) showed that the antilymphoma activity of guinea pig serum was relatively easily destroyed b y heating; in guinea pig serum kept at 56°C slight inactivation occurred, and at 66°C this became complete. Table I I I shows the result of an experiment in which a number of samples of guinea pig serum were incubated at varying temperatures for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) showed that the antilymphoma activity of guinea pig serum was relatively easily destroyed b y heating; in guinea pig serum kept at 56°C slight inactivation occurred, and at 66°C this became complete. Table I I I shows the result of an experiment in which a number of samples of guinea pig serum were incubated at varying temperatures for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…(Received for publication, April 3, 1963) The action of guinea pig serum in bringing about in vivo, the regression of 3 transplanted mouse and rat lymphomas was first described by Kidd in papers from this laboratory in 1953 (1,2). Several highly specific features were shown: first, that inhibition was produced only by guinea pig serum, sera from other animal species being completely devoid of effect.…”
mentioning
confidence: 99%
“…In 1953, Kidd (47,48) demonstrated that the growth of certain lymphomas is suppressed and regression of certain established tumors occurs when guinea pig serum is injected into mica and rats carrying the tumors. Interest in asparaginases was stimulated when it was found to be the tumor-suppressing agent in guinea pig serum (2, 6~ 7, 8,10,14,63,113).…”
Section: Asparaginase As An Antitumor Agentmentioning
confidence: 99%
“…Very few works are available that uses Ethidium bromide as a mutagen. Amena et al [76] performed Ethidium bromide mutagenesis on L-asparaginase producing Streptomyces gulbargensis but there were no productive mutants.…”
Section: Choice Of Mutagenmentioning
confidence: 99%
“…[14] A study also shows that when 4% of peptone was used as nitrogen source, high enzyme production was observed in Actinomycetes and Streptomyces griseus. [76] It was observed that the quantity of nitrogen source also affected enzyme production. Liu et al [89] gave evidence that when 0.05% yeast extract medium was used no yield was observed and when the concentration was increased to 3% complete inhibition of the enzyme yield was observed.…”
Section: Effect Of Nitrogen Sourcementioning
confidence: 99%